2016
DOI: 10.1111/1471-0307.12282
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and sensory properties of milk fortified with iron microcapsules prepared with water‐in‐oil‐in‐water emulsion during storage

Abstract: This study investigated the possibility of fortifying iron microcapsule powder into milk and the effects of the fortification on the physicochemical and sensory properties of the products during storage. The iron microcapsules were prepared by the water‐in‐oil‐in‐water (W/O/W) emulsion technique. Fortifying the lower concentrations (0.1–0.3%, w/v) of iron microcapsules into the milk samples did not significantly change thiobarbituric acid values. The L‐values for the milk samples were not significantly influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“… Rocha et al (2012) reported that microencapsulation protected the bioactive compounds in tomatoes from severe environmental conditions during food processing. Bioactive compounds have been successfully used in various dairy products, such as milk, cheese, and yogurt ( Chang et al , 2016 ; Kwak et al , 2016 ; Lee et al , 2013 ). These compounds display enhanced functional activities following microencapsulation.…”
Section: Introductionmentioning
confidence: 99%
“… Rocha et al (2012) reported that microencapsulation protected the bioactive compounds in tomatoes from severe environmental conditions during food processing. Bioactive compounds have been successfully used in various dairy products, such as milk, cheese, and yogurt ( Chang et al , 2016 ; Kwak et al , 2016 ; Lee et al , 2013 ). These compounds display enhanced functional activities following microencapsulation.…”
Section: Introductionmentioning
confidence: 99%
“…Double emulsions combine a high encapsulation efficiency potential with the ability to mask undesirable tastes in a simple, low‐cost method . Only a few studies have focused on encapsulating iron within water‐in‐oil (W/O) emulsions and within double emulsions . Although these studies have shown that double emulsions are suitable to encapsulate iron with a high and stable encapsulation efficiency (EE), and in amounts that are relevant to food fortification, they have also pointed out that the presence of iron in water droplets dispersed in oil largely favours lipid oxidation, which was to be expected due to the strong pro‐oxidant activity of iron …”
Section: Introductionmentioning
confidence: 99%
“…4 Only a few studies have focused on encapsulating iron within water-in-oil (W/O) emulsions [5][6][7] and within double emulsions. [7][8][9][10][11] Although these studies have shown that double emulsions are suitable to encapsulate iron with a high and stable encapsulation efficiency (EE), and in amounts that are relevant to food fortification, they have also pointed out that the presence of iron in water droplets dispersed in oil largely favours lipid oxidation, which was to be expected due to the strong pro-oxidant activity of iron. [12][13][14] Although attempts have been made at mitigating the pro-oxidant effect of encapsulated iron in such W/O or double emulsions, for example by increasing the solid fat content of the lipid phase, 5 the effect of other potentially determining factors, such as the water droplet size, remains unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Among the techniques for iron encapsulation, spray drying has been reported to efficiently immobilize ferrous sulfate using pea protein as the wall material (Bittencourt et al, 2013;Ferreira et al, 2011). Other studies report on the potential of emulsions, more specifically water-in-oil and double emulsions, for iron encapsulation (Chang et al, 2016;Choi et al, 2009;Dubey & Windhab, 2013;Prichapan et al, 2018;Simiqueli et al, 2019a;b), and indicate that those emulsions can encapsulate iron in concentrations that are relevant to food fortification, with a high and stable encapsulation efficiency.…”
Section: Controlling the Effect Of Iron On Protein Oxidationmentioning
confidence: 99%
“…Double emulsions combine a high encapsulation efficiency potential with the ability to mask undesirable tastes in a simple, low-cost method (Matos et al, 2015). Only a few studies have focused on encapsulating iron within water-in-oil (W/O) emulsions (Choi et al, 2009;Dubey & Windhab, 2013;Prichapan et al, 2018) and within double emulsions (Chang et al, 2016;Choi et al, 2009;Hosseini et al, 2019;Simiqueli et al, 2019a;b). Although these studies have shown that double emulsions are suitable to encapsulate iron with a high and stable encapsulation efficiency (EE), and in amounts that are relevant to food fortification, they have also pointed out that the presence of iron in water droplets dispersed in oil largely favours lipid oxidation, which was to be expected due to the strong prooxidant activity of iron (Jacobsen, 2016;Osborn & Akoh, 2003).…”
Section: Introductionmentioning
confidence: 99%